Explorations and Excavations in Turkey, 1963 - Alkım, Handan
ersch. 1965; 1. Prehistorical Research in Southeastern Anatolia (Urfa, Diyarbakır, Siirt); 2. The Region of Beyşehir-Suğla lakes district (Konya); 3. The Cave of Karain (Antalya); 4. Çatal Hüyük (Konya); 5. Can Hasan (Konya); 6. Information about prehistoric pottery at Tuzla (Istanbul); 7. The Hüyük between the Thermal Springs and the Cement Factory at Tuzla (Istanbul); 8. The Tumuli in the neighbourhood of Malkara and Keşan (Tekirdağ-Edirne); 9. The Dolmens of Lalapaşa-Büyünlü (Edirne); 10. Kültepe (Kayseri); 11. Tilmen Hüyük (Gaziantep); 12. Kara Hüyük (Konya); 13. Sema Hüyük (Antalya); 14. Müsgebi – Early Bronze Age (Muğla); 15. Acem-Hüyük (Aksaray-Niğde); 16. Müsgebi – Mycenaean (Bodrum-Muğla); 17. Alaca Hüyük (Çorum); 18. Boğazköy (Çorum); 19. Ilıca (Ayaş-Ankara); 20. Dirmil (Muğla); 21. The Cemetery at Ünsel, formerly Ernis/Arnıs (Van); 22. Evditepe Cemetery (Van); 23. The Cemetery of Alacahan (Van); 24. Altıntepe (Erzincan); 25. Toprakkale (Van); 26. Çavuştepe (Van); 27. Patnos (Ağrı); 28. Karatepe and Kadirli (Adana); 29. Yalıncak (Ankara); 30. Gordion (Ankara); 31. Iassos (Muğla); 32. The Letöon at Xanthos (Muğla); 33. Çandarlı; (34-48 griechisch-römische Ausgrabungsstätten); 34. Sardis (Manisa); (35-55 byzantinische und islamische Ausgrabungsstätten); 56. Exploration activities of the members of the British Institute of Archaeology at Ankara; (57-58 hellenistische Ausgrabungsstätten.